EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERHITUNG PADA MATERI OPERASI HITUNG CAMPURAN SEKOLAH DASAR - Theresia Ayu Wahyuningtyas; Ema Butsi Prihastari; Oka Irmade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigated the effectiveness of a problem-based learning model on thenumeracy skills of second-grade students at SD Negeri Kestalan, Surakarta. Theresearch was prompted by the persistent issue of low arithmetic abilities among students in the 21st century. Using a quantitative approach with a one-group pretest-posttest experimental design, the study involved 25 students as its subjects. Data was collected through tests, observations, and documentation, using instrumentsthat had been previously validated for their validity, reliability, discrimination power,and difficulty level. The data analysis, which included the Shapiro Wilk test, PairedSample T-Test, and N-Gain test, revealed that this learning model was quiteeffective in improving students' arithmetic skills, specifically in mixed operations.This finding is supported by a significance value of 0.000 (< 0.05) in the hypothesistesting and an N-Gain percentage of 65.6762%, which signifies a notableimprovement following the intervention. In conclusion, the implementation of theproblem-based learning model proved to be effective in boosting the arithmetic skillsof second-grade students in the specified subject matter.